Perioperative quality of care is modulated by process management with clinical pathways for fast-track surgery of the colon - Schwarzbach, Matthias; Hasenberg, Till; Linke, Miriam; Kienle, Peter; Post, Stefan; Ronellenfitsch, Ulrich (International journal of colorectal disease, 2011)
Clinical pathways (CPs) are increasingly used to improve quality of care. However, evidence if such improvements are also feasible in fast-track colorectal surgery is lacking. This study evaluates effects of a CP for fast-track colonic resections with respect to process and outcome quality.
Gesehen am 28.10.2022